1998
DOI: 10.1007/pl00009726
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NaCl salinity on growth and mineral partitioning in Quercus robur L., a rhythmically growing species

Abstract: Sodium salt sensitivity of common oak (Quercus robur L.) was evaluated in hydroponic culture using INRA-Morizet solution. Addition of NaCl to the nutrient solution reduced only length and weight of roots and first flush stems. In contrast, the second flush was properly expanded even in the presence of 40 mM of NaCl in culture medium. Both leaf number and leaf area were not affected by increasing salt concentration in medium culture while this increase induced significant leaf damage especially in first flush l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…In the control plants, the concentration of Cl À was higher in the roots than the leaves, while after 100 mmol l À1 NaCl the amount of Cl À was greater in the leaves. In some plant species, Cl À uptake and transport appears to be less controlled than Na + (Alaoui-Sossé et al, 1998). This has also been observed in Sorghum bicolor (Khan et al, 1995) and Cornus stolonifera (Renault et al, 2001), as well as in the present study where Cl À concentrations were higher than Na + concentrations in leaf tissues.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…In the control plants, the concentration of Cl À was higher in the roots than the leaves, while after 100 mmol l À1 NaCl the amount of Cl À was greater in the leaves. In some plant species, Cl À uptake and transport appears to be less controlled than Na + (Alaoui-Sossé et al, 1998). This has also been observed in Sorghum bicolor (Khan et al, 1995) and Cornus stolonifera (Renault et al, 2001), as well as in the present study where Cl À concentrations were higher than Na + concentrations in leaf tissues.…”
Section: Resultssupporting
confidence: 80%
“…The decrease in chlorophyll may be attributed to increased chlorophyllase activity (Sudhakar et al, 1997). It has also been reported that Cl À may be more injurious than Na + (Shannon et al, 1994), causing leaf chlorosis in several plant species (Alaoui-Sossé et al, 1998). In agreement with this, leaf chlorophyll a content was reduced significantly as a result of increasing Cl À (y ¼ À377.06x+2037; R 2 ¼ 0.89; po0.01) and Na + (y ¼ À1645.2x+2051.3; R 2 ¼ 0.41, po0.05) in leaves.…”
Section: Resultsmentioning
confidence: 96%
“…Trees with similar health status and similar Cl contents contained from 221 to 2083 mg/kg of Na. The toxic effects of Na on the woody vegetation were lower than those of Cl (Alaoui-Sosse et al 1998). This was confirmed by, among others, research conducted by Kayama et al (2003) on the effects of salinity on the vitality and health status of Picea abies and Picea glehnii.…”
Section: Discussionmentioning
confidence: 82%
“…However, there have been no studies on the effects of exogenous proline on forest species in vitro culture. It has been shown that the growth and physiological condition of oak, when grown in culture, was affected by NaCl, even at low concentration [1]. There have been no published studies on the effects of NaCl on cell cultures of gymnosperms.…”
Section: Introductionmentioning
confidence: 99%